Virtual Reality as a Pedagogical Tool: Motivation and Perception in Teacher Training for Social Sciences and History in Primary Education - Villena-Taranilla, Rafael; Diago, Pascual D.; Colomer Rubio, Juan Carlos (Education Sciences, 2025)
This study investigates the motivation of future primary education teachers when using virtual reality (VR) as a pedagogical tool for teaching Social Sciences and History. A total of 73 students participated, engaging with curricular content through an immersive experience designed to strengthen digital and methodological skills. Motivation was measured using a reduced version of the Instructional Material Motivational Survey (IMMS), assessing attention, relevance, confidence, and satisfaction. Additionally, an adaptation of the LOES-S questionnaire was used to analyze the perception of VR as a learning object in initial teacher training. On a Likert scale (1–5), the results showed a high overall motivation level (𝑀=4.56 , 𝑆𝐷=0.26 ), with satisfaction (𝑀=4.92 , 𝑆𝐷=0.20 ) being the most prominent factor. Relevance, however, received a lower score (𝑀=4.36 , 𝑆𝐷=0.44 ), suggesting difficulty connecting immersive content with prior knowledge. In the LOES-S questionnaire, engagement (𝑀=4.88 , 𝑆𝐷=0.27) was the highest-rated construct, indicating strong emotional and motivational involvement. No significant gender differences were found, emphasizing the inclusive nature of VR. This study highlights the potential of VR to enhance teacher training, motivation, digital competencies, and innovative methodologies, while underscoring the need for effective pedagogical design to optimize its educational impact.
Keywords: teacher motivation; virtual reality; initial teacher training; social sciences